Drop-the-p: Bayesian CFA of the Multidimensional Scale of Perceived Social Support in Australia - Santiago, Pedro Henrique Ribeiro; Quintero, Adrian; Haag, Dandara; Roberts, Rachel; Smithers, Lisa; Jamieson, Lisa (Frontiers in Psychology, 2021)
Aim: We aimed to investigate whether the 12-item Multidimensional Scale of Perceived Social Support (MSPSS) constitutes a valid and reliable measure of social support for the general adult Australian population. Methods: Data were from Australia’s National Survey of Adult Oral Health 2004-2006 and included 3,899 participants aged 18 years old and over. The psychometric properties were evaluated with Bayesian Confirmatory Factor Analysis. One factor, two-factor (Family and Friends subscales) and three-factor (Significant Other, Family and Friends) structures were tested. Model fit was assessed with the Posterior Predictive p-value (PPPX2), Bayesian Root Mean Square Error of Approximation (BRMSEA) and Bayesian Comparative Fit Index (BCFI). Dimensionality was tested by comparing competing factorial structures with the Bayes Factor (BF). Reliability was evaluated with the Bayesian OmegaH. Convergent validity was investigated with the PSS (Perceived Stress Scale) and discriminant validity with the PDC-3 (Perceived Dental Control scale). Results: The theoretical 3-factor model (Significant Other, Family and Friends) provided a good fit to the data (PPPX2 < 0.001, BRMSEA=0.089 - 95% CrI [0.088, 0.089]; BCFI=0.963 - 95% CrI [0.963, 0.964]). The BF provided decisive support for the three-factor structure in relation to the other two structures (BF31 = 5.94*103409, BF32 = 9.22*102005). The SO (BOmegaH=0.95 - 95% CrI [0.90, 0.99]), FA (BOmegaH=0.92 - 95% CrI [0.87, 0.97]) and FR (BOmegaH=0.92 - 95% CrI [0.88, 0.97]) subscales displayed excellent reliability. The MSPSS displayed the expected pattern of convergent and discriminant validity. Conclusion: The MSPSS demonstrated good psychometric properties and excellent reliability in a large Australian sample. This instrument can be applied in national surveys and provide evidence of the role of social support in the Australian population.